2018
DOI: 10.1002/hpm.2716
|View full text |Cite
|
Sign up to set email alerts
|

Does the agglomeration effect occur in the hospital sector? The impact of agglomeration economies on the financial performance of hospitals—An evidence from Poland

Abstract: Summary The main aim of the article is to analyze the occurrence of agglomeration effect in the hospital sector on the basis of financial performance. The considerations are made on the example of hospitals in Poland—the country that survived the latest economic crisis relatively well, usually generating positive values of GDP, but where still there is an ongoing discussion on the final shape of healthcare financing model. The article is based on the assumption that there occur significant differences in finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Several recently published studies have been focused on financial performance of hospitals in Poland [29][30][31]. Yet these covered a limited number of hospitals, based on their specialty and/or geographical location.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several recently published studies have been focused on financial performance of hospitals in Poland [29][30][31]. Yet these covered a limited number of hospitals, based on their specialty and/or geographical location.…”
Section: Introductionmentioning
confidence: 99%
“…The authors compared financial indicators between urban and rural hospitals, concluding that the latter are characterized by better financial condition [29]. Krzeczewski et al (2019) conducted a longitudinal study (2007-2016) on a group of 118 hospitals, comparing financial performance of units from big vs. smaller cities. The results indicated that hospitals located in cities with a population above 100,000 people perform better financially than those from smaller cities [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14][15] The complementary studies on responses to the deterioration of health facilities' financial performance have focused on hospitals, as they consume a substantial share of public health expenditures. 3,[16][17][18][19] For example, a study from Poland indicated that a mix of both system and micro-level factors contributed to undermining public hospital financial standing, with poor management, weak owner control, and the state of hospital infrastructure being the lead factors at a facility level. 1 The literature is also scarce on approaches used to deal with debts and liabilities of public PHC facilities or improve their financial sustainability in the contexts similar to RS.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the available papers elaborated on cases of facilities in European post‐socialist countries 10‐15 . The complementary studies on responses to the deterioration of health facilities' financial performance have focused on hospitals, as they consume a substantial share of public health expenditures 3,16‐19 . For example, a study from Poland indicated that a mix of both system and micro‐level factors contributed to undermining public hospital financial standing, with poor management, weak owner control, and the state of hospital infrastructure being the lead factors at a facility level 1 .…”
Section: Introductionmentioning
confidence: 99%